A lateral pós-vocálica em coda silábica: um panorama da velarização em contato dialetal - Santos, Ohana Soara Andrade (2020)
Dialectal contact is a phenomenon that is present in the linguistic and cultural background of Guineans since their birth, because of the origin of their mother tongue and Guinean Creole, which arose through the contact between ethnic African languages and European Portuguese. The present work proposes to analyze the production of the lateral consonant /l/ in syllabic coda, by Guinean speakers living in Brazil. We work under the hypothesis that this consonant behaves, in most cases, in a velarized form, assuming a linguistic characteristic of Guinean speakers, while Brazilians produce it, mostly, in a vocalized form. The research is based, above all, on the dialectal contact between Brazilian Portuguese and Guinean Creole and, based on that, it seeks to prove the major occurrence of velarization in the realization of Guineans through investigative methods based on the theory of language variation, highlighting the extralinguistic influences affecting the syllable restructuring process. For conducting the research, recorded interviews based on Tarallo (2005) and Labov ([1966] 2008) were used as corpus with regard to the structure and conduct of the interviews, which were organized based on thematic modules consistent with the social and linguistic reality of the informants. Authors such as Labov ([1966] 2008), to address Variationist Sociolinguistics, Fernández (1998), Chacon (2012), Lucena (2017) and Silva (2013) on matters of dialectal contact. Through the encoding of all the data, run in the GoldVarbX program, all the established linguistic and extralinguistic variables were compared. The results we reached show us that Guinean students with the longest exposure/residency in Brazil continue to use the lateral /l/ in velarized form obtaining very high velarization values.